2002
DOI: 10.1038/sj.bjc.6600207
|View full text |Cite
|
Sign up to set email alerts
|

Role of proteolytic enzymes in human prostate bone metastasis formation: in vivo and in vitro studies

Abstract: Prostate cancers ability to invade and grow in bone marrow stroma is thought to be due in part to degradative enzymes. The formation of prostate skeletal metastases have been reproduced in vitro by growing co-cultures of prostatic epithelial cells in bone marrow stroma. Expression of urokinase plasminogen activator, matrix metalloproteinase 1 and 7 by prostatic epithelial cells were identified using immunocytochemistry. Also, in vivo tissue sections from human prostatic bone marrow metastases were stained. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 25 publications
3
33
0
Order By: Relevance
“…The primary fibroblast and osteoblast MMPs found in our assays were MMP-1 and -2. We found no MMP-3 or -7; however, the absence of these MMPs in some prostate cancer cell lines including PC-3 20,37,38 and osteoblasts 3,39 is consistent with previous reports.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The primary fibroblast and osteoblast MMPs found in our assays were MMP-1 and -2. We found no MMP-3 or -7; however, the absence of these MMPs in some prostate cancer cell lines including PC-3 20,37,38 and osteoblasts 3,39 is consistent with previous reports.…”
Section: Discussionsupporting
confidence: 93%
“…This process appears to be regulated to a large extent by the matrix metalloproteinases (MMPs) and plasminogen activators (PAs). 1,2 Several MMPs have been linked to prostate cancer metastasis including MMP-1, 3 -2 and -9, 4,5 -3, 6 -7 3,7 and -14. 8 Many MMPs contributing to tumor invasion are produced primarily by stromal cells; 9 however, prostate cancer cell production of specific MMPs such as MMP-9 can also play essential roles.…”
Section: Introductionmentioning
confidence: 99%
“…MMPs are zinc-containing endopeptidases that degrade extracellular matrix components and are associated with cancer cell invasion and metastasis (Egeblad and Werb, 2002). It was suggested that upregulation of MMP-1 is an Wnt5a and aggressiveness of prostate cancer H Yamamoto et al important factor in the aggressiveness of PCa and bone marrow metastasis (Hart et al, 2002). This study showed that knockdown of MMP-1 indeed suppressed Wnt5a-dpendent invasion of PC3 cells in vitro.…”
Section: Mechanism By Which Wnt5a Promotes Aggressiveness Of Pcamentioning
confidence: 70%
“…We have also shown that trans-endothelial migration by prostate epithelial cells induces the invasion of bone marrow endothelial cells across the Matrigel basement membrane. The exact nature of this basement membrane invasion by the bone marrow endothelial cells is unknown but may be a result of the weakening of the basement membrane itself due to prostate epithelial proteolytic secretions, a phenomenon known to occur during prostate epithelial migration and metastasis (Hart et al, 2002). However, Figure 4B shows that in the presence of both PNT2-C2 and BPH there is significant BMEC invasion without epithelial invasion, which suggests that the overall integrity of the basement membrane has remained intact.…”
Section: Discussionmentioning
confidence: 96%
“…Initial steps include the loss of cell-to-cell adhesion within the tumour by downregulation of molecular binding complexes such as the E-cadherin/b-catenin complex (Umbas et al, 1997;Bryden et al, 2002) and intravasation of tumour cells through the basement membrane by production of enzymes such as matrix metalloproteinases (Hart et al, 2002). Once in the peripheral blood, the circulating tumour cell has to bind at its preferred metastatic site and invade through the local endothelial barrier to gain access to the underlying stroma (Scott et al, 2001) where it can then become established (Lang et al, 1997(Lang et al, , 1998.…”
mentioning
confidence: 99%